SOCIO-PSYCHOLOGICAL ASPECTS OF WAR AND THEIR TRANSGENERATIONAL DIMENSION - Yordanova, Kalina (Journal of Sociology: Bulletin of Yerevan University, 2024)
This paper is about the psychological effect of war. By the welding of the explanatory potential of psychoanalysis and anthropology, it argues that victims of armed conflict, particularly if protracted, construct a melancholic response (Yordanova, 2018). Often, people on the move are met with hostility by the host countries or may find themselves in the social periphery. This fosters ambivalence towards the new environment as an expression of vulnerabilities. The paper suggests an intergenerational aspect to the above dynamic, too. Children, exposed to violence, lack the emotional and cognitive maturity to grasp what they have lived through. Yet, overwhelmed with their own feelings of loss, their parents fail to help them deal with the trauma. Thus, children identify with the parents’ complicated grief and the assumption of an idealized pre-war past versus scarce future opportunities. Finally, the paper examines the intersections between individual war trauma, cultural memory and power dynamics in post-conflict societies. Using my field work in Sarajevo (2012, 2018), I argue that war survivors avoid the construction of a consistent war narrative in the first person because they need the state-recognized version of history to be re-written (Yordanova, 2015). The ambiguity of their experience in war, the inadequacy of language to convey horror, and the clash of private memories with the official discourse drive them to alternative forms of expression. Survivors and their children use art, humour, tattoos, scarring, and landscape to explain the war and get connected to each other. In the post-war environment, the narrative of veterans who were most exposed to warfare becomes muted in order not to challenge the political status-quo.